A Model Suggestion for Determining the Values of Firms the Energy Sector: An Application in BIST Electricity Index - Turan Kurtaran, Ayten; Günay, Burhan; Kurtaran, Ahmet (International Journal of Energy Economics and Policy, 2021)
Investors in financial markets have recently sought rational investment decisions with advanced technology and information obtained from various sources. Therefore, investors need to accurately determine the value of the firm. The value of companies in the energy sector contains different dynamics than companies in other sectors. The aim of this study is to develop models that best represent the values of companies in the energy sector and make them available to shareholders. For this purpose, OLS regression and Panel Data Analysis were used in the study. The data of the models to be tested in the study were obtained from the data of 11 companies traded in the Borsa Istanbul (BIST) Electricity Index between 2009-2018. In the analysis of the study, 3 models, namely Market to Book Value, Standardized Economic Value Added and Standardized Market Value Added, were created to represent the company value, and the model that best represents the company value for the shareholder was presented. Keywords: Panel Data Analysis, Economic Value Added, Market Value, Market Value Added, Energy Sector JEL Classifications: G20, G32, M41, Q43 DOI: https://doi.org/10.32479/ijeep.11520